Pharmacokinetic-pharmacodynamic profile of systemic nitric oxide-synthase inhibition with L-NMMA in humans - Mayer, Bernhard X (Blackwell Science Inc, 1999)
AIMS: It has been demonstrated that inhibition of endothelium derived nitric oxide with N(G)-monomethyl-l-arginine (l-NMMA) results in a different cardiac and peripheral vascular response. The purpose of this study was to investigate the pharmacokinetic-pharmacodynamic profile of l-NMMA and pharmacokinetic interactions with l-arginine in healthy subjects. METHODS: Plasma pharmacokinetics were analysed from two different studies: In study 1, 3 mg kg(−1) l-NMMA was administered i.v. over 5 min and systemic haemodynamics, cardiac output (CO), fundus pulsation amplitude (FPA), and NO-exhalation (exhNO) were measured at baseline and 15, 65, 95, 155, and 305 min after start of drug administration (n=7). In study 2, 17 mg kg(−1) min(−1) of the physiologic substrate for nitric oxide synthase, l-arginine, was coinfused i.v. over 30 min with a primed constant infusion of 50 μg kg(−1) min(−1) l-NMMA (n=8). RESULTS: Bolus infusion of l-NMMA resulted in a maximum plasma concentration of 12.9±3.4 μg ml(−1) (mean±s.d.) with elimination half-life of 63.5±14.5 min and clearance of 12.2±3.5 ml min(−1) kg(−1) and caused a small hypertensive response, decreased CO by 13%, FPA by 26%, exhNO by 46% and increased systemic vascular resistance by 16% (P<0.05 each) 15 min after start of drug administration. Although only limited data points were available in the l-NMMA plasma concentration range between 0 and 4 μg ml(−1), drug effects over time were in good agreement with an E(max) model (r(2)>0.98 each), which also suggested that concentrations producing half-maximum effects were higher for FPA than for CO and exhNO. The coinfusion with l-arginine caused a nearly two-fold increase in plasma l-NMMA levels, indicating a pharmacokinetic interaction. CONCLUSIONS: In the absence of a systemic hypertensive response, l-NMMA significantly decreased CO, exhNO, and FPA. The concentration calculated to produce a half maximal effect was equivalent for exhNO and CO, but markedly higher for FPA. Furthermore, measurement of FPA is susceptible to changes in l-NMMA levels at small plasma concentrations.